Pemikiran Universalisme Islam Nurcholish Madjid dan Relevansinya Terhadap Penyelenggaraan Pendidikan Multikultural - Arifa, Laily Nur (AL-WIJDÃN Journal of Islamic Education Studies, 2017)
Indonesia has one of the world’s cultural diversity. Indonesia’s diversity like a double-edged knife. Besides as excellence, diversity leads to many conflicts. To prevent such conflicts occur, the necessary awareness of multicultural effective if implanted through education. Moreover, religion also has an important role in keeping the peace. Islamic religion has a concept of Islam Rahmatan li al-’âlamîn, the universal teachings of Islam which teaches followers to live peacefully side by side and keep the peace. Universal Islam is most often expressed by Nurcholish Madjid. Islamic universalism in view Nurcholish Madjid have the same ‘spirit’ with multicultural education as follows; (A) Award in diversity, manifested in; first, the diversity of languages. Secondly, respect for the diversity of religions and beliefs. Third, respect for ethnic diversity, can be realized through a narrative that multiethnic, analogy, and excursions. (B) Social Justice, embodied in education and justice and equal rights to education. (C) Wisdom-Based Local Culture. The implication can be realized in various forms, first, in the form of the use of instructional media puppet show, angklung or ludruk. Second, in the curriculum, such as local content batik expertise, integration with subjects and extrabased local culture. (D) Investment attitude of ‘Islam’ as a basis for multicultural behavior. An important point which has apparently not yet been applied at planting multicultural attitude is consciousness ‘Islam’ (with ‘i’ minor) in individual behavior. attitude of ‘Islam’ which means Nurcholish means submission and surrender to God will bring the man no longer be the most righteous judge in the world, and appreciate diversity as a sunnatullah. Keywords: Nurcholish Madjid, Islamic universalism, Multicultural Education